Lipoprotein (a) in atherosclerosis: A bibliometric and visualization analysis - Hui Wang; Dikang Pan; Lianming Liao; Sensen Wu; Lefan Hu; Hanyu Zhang; Yachan Ning; Jianming Guo; Yongquan Gu (Vascular Investigation and Therapy, 2023)
Lipoprotein (a) [Lp (a)] is a complex polymorphic lipoprotein consisting of one low-density lipoprotein particle with one molecule of apolipoprotein B100 and another apolipoprotein (a) linked by a disulfide bond. In recent years, due to its causal role in premature atherosclerotic cardiovascular diseases and calcified aortic stenosis, Lp (a) has attracted more and more attention. Our study aimed to illustrate the trend of Lp (a) research in atherosclerosis (AS) through bibliometric analysis. The Science Citation Index-Expanded was used to locate Lp (a) and AS studies published between December 1, 2012 and December 1, 2022. VOSviewer and CiteSpace bibliometric software packages were used to analyze literature information. LP (a) has seen an overall increase in annual publications. The United States had the highest number of publications worldwide, with 192 publications. The University of California, San Diego, has contributed significantly to Lp (a) with 29 publications and led research collaboration. In the past few decades, there has been close collaboration between countries or regions, institutions, and authors. In addition, the European Heart Journal was the most cited, followed by the Journal of Lipid Research and AS with 2033, 1096, and 806 citations, respectively. Recent studies were on genes and lipid-lowering therapies. Our study comprehensively evaluated the research status and trends of Lp (a) in AS worldwide for the first time and provided a valuable reference for clinical researchers.